2001
DOI: 10.1038/sj.bmt.1703200
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the use of high-dose melphalan with autologous stem cell transplantation for the treatment of AL amyloidosis

Abstract: Summary:Primary or AL amyloidosis results from a plasma cell dyscrasia in which fibrillar light chain protein deposition leads to organ failure and death. Standard treatment for AL amyloidosis has been oral melphalan and prednisone. However, this form of treatment modifies the natural history of this lethal disease only marginally, extending median survival from 13 months following diagnosis to 17 months. At Boston University Medical Center, we have developed treatment protocols using high-dose intravenous mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
123
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(136 citation statements)
references
References 13 publications
4
123
0
5
Order By: Relevance
“…One must consider the occasional possibility of a monoclonal gammopathy incidentally associated with AF or SSA. The application of chemotherapy to a patient with a nonimmunoglobulin form of amyloid is contraindicated [53], would provide no benefit, and could be harmful to the patient [54].…”
Section: How Is the Amyloidosis Characterized As Al Type?mentioning
confidence: 99%
“…One must consider the occasional possibility of a monoclonal gammopathy incidentally associated with AF or SSA. The application of chemotherapy to a patient with a nonimmunoglobulin form of amyloid is contraindicated [53], would provide no benefit, and could be harmful to the patient [54].…”
Section: How Is the Amyloidosis Characterized As Al Type?mentioning
confidence: 99%
“…Numerous reports have described the availability of autologous PBSCT for systemic AL amyloidosis, but some reviews have reported high TRMs (13-39%) in autologous PBSCT for systemic AL amyloidosis [2][3][4][5][6][7]. Comenzo and Gertz [4] described TRM rates approaching 100% in patients with cardiac amyloidosis and clinical congestive heart failure or history of arrhythmia, syncope, or recurrent pleural effusion.…”
Section: Discussionmentioning
confidence: 99%
“…These are, to our knowledge, the first cases of splenic rupture in AL amyloidosis as a complication of HDM/SCT. HDM/SCT is the treatment of choice for a subset of patients with AL amyloidosis since this treatment has been shown to induce complete hematologic remissions and to reverse amyloid-related disorders [8,34]. G-CSF is widely used to mobilize peripheral progenitor cells for collection by leukapheresis prior to HDM/SCT as well as to accelerate hematopoietic recovery in the peritransplant period.…”
Section: Discussionmentioning
confidence: 99%
“…He received prophylactic benzylpenicillin for 6 months after HDM/SCT. At 1 year following treatment with HDM/SCT, he was found to have achieved a complete hematologic remission, defined as absence of monoclonal gammopathy in serum and urine by immunofixation electrophoresis and a normal bone marrow biopsy showing less than 5% plasma cells with no evidence of clonal predominance [8].…”
Section: Case Reportsmentioning
confidence: 99%